Pembentukan kokristal Ketoprofen-Urea-NaCl untuk Peningkatan Sifat Kelarutan - Laily, Aisyah Prida; Irawan, Eka Deddy; Wisudyaningsih, Budipratiwi; Barikah, Kuni Zu’aimah; Wicaksono, Yudi (Journal of Agropharmacy, 2024)
Ketoprofen is a potent non-steroidal anti-inflammatory drug compound but is difficult to dissolve in water. This research aims to increase the solubility of ketoprofen through cocrystallization using a urea coformer with the addition of the inorganic salt NaCl. Cocrystallization was carried out using the solvent evaporation method using methanol. The characterization of the cocrystal results included PXRD, DSC, and FTIR. At the same time, the solubility evaluation was carried out using a solubility test in distilled water and a dissolution test in phosphate buffer media pH 7.4. The results showed that ketoprofen forms a cocrystal with the urea coformer, whereas adding NaCl produces a ketoprofen-urea-NaCl cocrystal with a lower crystallinity and melting point. The solubility of ketoprofen-urea-NaCl cocrystals in distilled water was 183.82 ± 2.84 mg/L, while ketoprofen-urea and ketoprofen cocrystals were 174.23 ± 6.83 and 171.12 ± 6.29 mg/L, respectively. The dissolution test in phosphate buffer medium pH 7.4 showed the dissolution rate of ketoprofen-urea-NaCl cocrystals > ketoprofen-urea cocrystals > ketoprofen.